Gambaran Tingkat Compassion Fatigue Guru Bk Di Madiun - Dwi Sri Rahayu; Setyorini Setyorini; Nila Zaimatus Septiana; Alfin Mifathul Khairi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
The dynamics of compassion fatigue is when the counselor is no longer able to show compassion, care and empathy for the counselee. This is because the counselor experiences serious physical and emotional exhaustion as a result of continuous exposure to the counselor with counselees who have deep emotional pain. The purpose of this study was to describe the compassion fatigue of Middle School Guidance and Guidance Teachers in Madiun City. The research method used is a descriptive method with survey techniques. The participants in this study were all BK SMP teachers in Madiun City, totaling 69 BK teachers. The data collection tool used is the Compassion Satisfaction and Fatigue (CFT) Test scale adapted from Charles R. Figley. The data analysis technique used is categorization according to Azwar. The results of the study showed that junior high school counseling teachers in the city of Madiun experienced moderate level of compassion fatigue.